2013
DOI: 10.1111/febs.12439
|View full text |Cite
|
Sign up to set email alerts
|

Structure of NADP+‐dependent glutamate dehydrogenase from Escherichia coli – reflections on the basis of coenzyme specificity in the family of glutamate dehydrogenases

Abstract: Summary Glutamate dehydrogenases (EC 1.4.1.2–4) catalyse the oxidative deamination of l-glutamate to α-ketoglutarate using NAD+ and/or NADP+ as a cofactor. Subunits of homo-hexameric bacterial enzymes comprise a substrate-binding Domain I followed by a nucleotide binding Domain II. The reaction occurs in a catalytic cleft between the two domains. Although conserved residues in the nucleotide-binding domains of various dehydrogenases have been linked to cofactor preferences, the structural basis for specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 34 publications
5
24
0
Order By: Relevance
“…S2) with other NADP + /NAD + -specific GDHs and a few extra amino acid insertions. The overall structural fold of AnGDH is similar to the previously determined structures of E. coli GDH (EcGDH) and other GDHs (7,12,(21)(22)(23). Each subunit of AnGDH consists of two domains separated by a deep cleft (Fig.…”
Section: Structural Fold Of Angdh ̶ ̶supporting
confidence: 78%
See 2 more Smart Citations
“…S2) with other NADP + /NAD + -specific GDHs and a few extra amino acid insertions. The overall structural fold of AnGDH is similar to the previously determined structures of E. coli GDH (EcGDH) and other GDHs (7,12,(21)(22)(23). Each subunit of AnGDH consists of two domains separated by a deep cleft (Fig.…”
Section: Structural Fold Of Angdh ̶ ̶supporting
confidence: 78%
“…The NADP + -specific bacterial/fungal GDHs and the dual coenzyme specific mammalian GDHs are hexameric (12). The NAD + -dependent bacterial/fungal enzymes are either homohexamers (13) or homo-tetramers (14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike D-LDHs, which are all reported to be NAD ϩ dependent to date, three types of GDHs have been identified: NAD ϩ dependent, NADP ϩ dependent, and dual-nucleotide specific (32). As DLDH744 could use both NADH and NADPH with high efficiencies and even with a preference for NADPH as the coenzyme both in vitro and in vivo, protein structures were first compared for DLDH744 and GDHs.…”
Section: Discussionmentioning
confidence: 99%
“…Consequentially, the focus of the study was shifted to investigating the difference between DLDH744 and other reported NAD-linked LDHs with experimentally verified functionalities. It was reported that primary sequence alone is not a reliable guide for predicting coenzyme specificity (32). Cofactor specificity appears to be a function of the arrangement of secondary structural elements.…”
Section: Discussionmentioning
confidence: 99%